Lithium response in bipolar disorder is associated with focal adhesion and PI3K-Akt networks: a multi-omics replication study - Anna H. Ou; Sara B. Rosenthal; Mazda Adli; Kazufumi Akiyama; Nirmala Akula; Martin Alda; Azmeraw T. Amare; Raffaella Ardau; Bárbara Arias; Jean-Michel Aubry; Lena Backlund; Michael Bauer; et al. (Translational Psychiatry, 2024)
Abstract Lithium is the gold standard treatment for bipolar disorder (BD). However, its mechanism of action is incompletely understood, and prediction of treatment outcomes is limited. In our previous multi-omics study of the Pharmacogenomics of Bipolar Disorder (PGBD) sample combining transcriptomic and genomic data, we found that focal adhesion, the extracellular matrix (ECM), and PI3K-Akt signaling networks were associated with response to lithium. In this study, we replicated the results of our previous study using network propagation methods in a genome-wide association study of an independent sample of 2039 patients from the International Consortium on Lithium Genetics (ConLiGen) study. We identified functional enrichment in focal adhesion and PI3K-Akt pathways, but we did not find an association with the ECM pathway. Our results suggest that deficits in the neuronal growth cone and PI3K-Akt signaling, but not in ECM proteins, may influence response to lithium in BD.